Respostas
respondido por:
2
5x² + 25x + 3 = 0
a = 5; b = 25; c = 3
Δ = b² - 4ac
Δ = 25² - 4.5.3
Δ = 625 - 20.3
Δ = 625 - 60
Δ = 565
x = - b +/- √Δ = - 25 +/- √565
2a 2.5
x' = - 25 + √565 = - 25 + √565 = - 5 + √565
10 10 10 2 10
x" = - 25 - √565 = - 25 - √565 = - 5 - √565
10 10 10 2 10
565: 5
113: 113
1
__________________________________
Soma = - b = - 25 = - 5
a 5
Produto = c = 3
a 5
a = 5; b = 25; c = 3
Δ = b² - 4ac
Δ = 25² - 4.5.3
Δ = 625 - 20.3
Δ = 625 - 60
Δ = 565
x = - b +/- √Δ = - 25 +/- √565
2a 2.5
x' = - 25 + √565 = - 25 + √565 = - 5 + √565
10 10 10 2 10
x" = - 25 - √565 = - 25 - √565 = - 5 - √565
10 10 10 2 10
565: 5
113: 113
1
__________________________________
Soma = - b = - 25 = - 5
a 5
Produto = c = 3
a 5
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás